Double Track and Anti-SLAPP: Indonesian Judicial Reasoning in Environmental Cases - Deo Renaldi Saputra; Ali Mashyar; Cahya Wulandari; Sunusi Dauda; Yusril Ihza Mahendra (Walisongo Law Review (Walrev), 2026)
Abstract: This study examines the application of the double track system and the anti-SLAPP principle in Indonesian criminal law, with a focus on Decision Number 374/Pid.Sus/2024/PT SMG. The research addresses two questions: how the double track system operates in cases involving environmental defenders, and to what extent the anti-SLAPP principle influences judicial reasoning. A normative juridical approach is employed using statutory, conceptual, and case-based analysis of relevant legal instruments, doctrines, and court decisions. The findings show that the court may acknowledge the formal fulfillment of criminal elements while refraining from imposing punishment when the act is closely linked to environmental advocacy and public interest. The integration of the double-track system and the anti-SLAPP principle supports a more proportional and context-sensitive approach to criminal adjudication. The case analysis also reveals limitations, including the absence of clear procedural standards and the risk of inconsistent application across similar cases. Additionally, the protection of environmental defenders is not absolute and must be balanced with the rights of affected individuals. This study proposes a more structured integration of both principles to strengthen legal certainty, ensure proportionality, and support the protection of environmental defenders within a balanced framework of criminal justice. Studi ini meneliti penerapan sistem jalur ganda dan prinsip anti-SLAPP dalam hukum pidana Indonesia, dengan fokus pada Keputusan Nomor 374/Pid.Sus/2024/PT ​​SMG. Penelitian ini membahas dua pertanyaan: bagaimana sistem jalur ganda beroperasi dalam kasus-kasus yang melibatkan pembela lingkungan, dan sejauh mana prinsip anti-SLAPP memengaruhi penalaran yudisial. Pendekatan yuridis normatif digunakan dengan menggunakan analisis hukum, konseptual, dan berbasis kasus dari instrumen hukum, doktrin, dan keputusan pengadilan yang relevan. Temuan menunjukkan bahwa pengadilan dapat mengakui pemenuhan formal unsur-unsur pidana sambil menahan diri dari menjatuhkan hukuman ketika tindakan tersebut terkait erat dengan advokasi lingkungan dan kepentingan umum. Integrasi sistem jalur ganda dan prinsip anti-SLAPP mendukung pendekatan yang lebih proporsional dan peka konteks terhadap peradilan pidana. Analisis kasus juga mengungkapkan keterbatasan, termasuk tidak adanya standar prosedural yang jelas dan risiko penerapan yang tidak konsisten di berbagai kasus serupa. Selain itu, perlindungan pembela lingkungan tidak bersifat mutlak dan harus diseimbangkan dengan hak-hak individu yang terdampak. Studi ini mengusulkan integrasi yang lebih terstruktur dari kedua prinsip tersebut untuk memperkuat kepastian hukum, memastikan proporsionalitas, dan mendukung perlindungan para pembela lingkungan dalam kerangka peradilan pidana yang seimbang.            Keywords: Environmental Defender; Double Track System; Anti-SLAPP; Criminal Sanction; Judicial Decision.